MOPOELA WAW MOPOOPATATO : BENTUK PENINGKATAN PEMAHAMAN HAK-HAK KESEHATAN BAGI MASYARAKAT SEBAGAI PEKERJA DI DESA MALEO - Dungga, Weny Almoravid; Arief, Supriyadi A (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The people of Maleo village who work in several companies in Maleo village and its surroundings are less aware of the health rights that must be obtained while working in the company. Therefore, this community service is carried out in the form of Observation and Data Collection, legal counseling, focus group discussions and the preparation of SOPs for complaints regarding the fulfillment of workers' rights. The results of the community service carried out by this team The results of the community service carried out by the community service team after carrying out various community service programs are the existence of valid data on the number of people in Maleo village who work in several companies around Maleo village, the formation of community understanding and knowledge of the health rights that must be obtained by every worker, the knowledge of various problems of fulfillment of rights experienced by workers, and the formation of SOPs for complaints and follow-up handling of problems of fulfillment of rights that are specifically related to the health rights of workers.